Maternity uncertainty in cobreeding beetles: females lay more and larger eggs and provide less care. (18th February 2020) - Richardson, Jon; Smiseth, Per T
Abstract: Cobreeding, which occurs when multiple females breed together, is likely to be associated with uncertainty over maternity of offspring in a joint brood, preventing females from directing resources towards their own offspring. Cobreeding females may respond to such uncertainty by shifting their investment towards the stages of offspring development when they are certain of maternity and away from those stages where uncertainty is greater. Here we examined how uncertainty of maternity influences investment decisions of cobreeding females by comparing cobreeding females and females breeding alone in the burying beetle, Nicrophorus vespilloides . In this species, females sometimes breed together on a single carcass but females cannot recognize their own offspring. We found that cobreeding females shifted investment towards the egg stage of offspring development by laying more and larger eggs than females breeding alone. Furthermore, cobreeding females reduced their investment to post-hatching care of larvae by spending less time providing care than females breeding alone. We show that females respond to the presence of another female by shifting allocation towards egg laying and away from post-hatching care, thereby directing resources to their own offspring. Our results demonstrate that responses to parentage uncertainty are not restricted to males, but that, unlike males, females respond by shifting their investment to different components of reproduction within a single breeding attempt. Such flexibility may allow females to cope with maternity uncertainly as well as a variety of other social or physical challenges. Abstract : Cobreeding female burying beetles lay more and larger eggs and provide less care after hatching than females breeding on their own. Cobreeding with another female generates uncertainty over the maternity in a joint brood because females cannot identify their own offspring. We show that cobreeding females respond to this uncertainty by shifting their investment towards egg production because they are certain to invest in their own offspring.